Family Firms and the Choice of Payment Method in Domestic and International Acquisitions - Bouzgarrou, Houssam; Navatte, Patrick (Management international / International Management / Gestiòn Internacional, 2014)
This paper investigates the impact of family control on domestic and international acquisition’s payment. This effect is important to understand since it will underpin all the future financial flexibility of the merged firms in a context of accelerating international market integration. We find that the percentage of cash payment in acquisitions is positively associated with family voting rights, but we highlight that family wedge is negatively associated with cash payment, which indicates the important role of control-enhancing mechanisms. Dilution risk is crucial at an intermediate level of control, since this relationship is nonlinear. Moreover, we show that both unused debt capacity and the increase in debt capacity are used by family firms to finance the relevant deals, but that these firms become overleveraged after merging, losing some financial flexibility in exchange for equity control purposes.